Combination of Kalman filter and least-error square techniques in power system - Agha Zadeh, R.; Ghosh, Arindam; Ledwich, G. (IEEE Power Engineering Society, 2010)
An algorithm based on the concept of combining Kalman filter and least-error square (LES) techniques is proposed in this paper. The algorithm is intended to estimate signal attributes like amplitude, frequency and phase angle in the online mode. This technique can be used in protection relays, digitalAVRs, DGs, DSTATCOMs, FACTS, and other power electronics applications. The Kalman filter is modified to operate on a fictitious input signal and provides precise estimation results insensitive to noise and other disturbances. At the same time, the LES system has been arranged to operate in critical transient cases to compensate the delay and inaccuracy identified because of the response of the standard Kalman filter. Practical considerations such as the effect of noise, higher order harmonics, and computational issues of the algorithm are considered and tested in the paper. Several computer simulations and a laboratory test are presented to highlight the usefulness of the proposed method.Simulation results show that the proposed technique can simultaneously estimate the signal attributes, even if it is highly distorted due to the presence of nonlinear loads and noise.